Examines The Impact of Product And Service Quality On Customer Satisfaction at PT. BMTP With Personal Branding - Andi Nadirah M.; Indrawan; Parintak, Suparman; Attas, Anne; Harahap, Burhanuddin (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Factors such as the bank's reputation, visualization of logo and visual identity, communication with consumers, and the unity between the brand's commitment and the customer's real-life encounter. Personal branding refers to the perception and reputation of the bank's employees or representatives as individuals. However, there has been no concrete research on the effect of all three of these factors affects customer satisfaction.Purpose: The objective of this study is to fill the void in current research. Knowledge gap and a better understanding of the correlation between the quality of a product as well as the quality of service, and the establishment of a personal brand with customer satisfaction.Design/methodology/approach: This study utilized quantitative research methods to perform statistical tests, namely multiple linear regression analysis, employing the Structural Equation Modeling (SEM) approach with the SmartPLS tool. This research was conducted at PT. BMTP, data collected from November to December 2023. The research sample was 120 customer respondents, Data was collected by administering a questionnaire with structure to the respondents based on the scale known as the Likert.Findings/Result: The results of the conducted study research and hypothesis tests indicated a positive and significant direct impact on variable product quality on variable personal branding, variable quality of service on variable personal branding, and variable personal branding on customer satisfaction. Indirectly, the variable product quality positively and significantly impacts customer satisfaction through intervening variable personnel branding. The variable quality of service positively and significantly impacts customer satisfaction through the intervening variable of personal branding. Conclusion: The study's findings also indicate that personal branding plays a mediating role in the relationship between product and service quality and customer satisfaction. Originality/value (State of the art): Personal branding can improve customers' perceptions of the company's product and service quality, leading to increased customer satisfaction. Keywords: business competition, banking business, customer access, customer retention, positive brands, purchasing services